The Role of Influencers During the Covid-19 Pandemic on Social Media Instagram - Fathonah Annisa; Andi Alimuddin Unde; Muhammad Farid (Research Synergy Foundation, 2021)
During the Covid-19 pandemic, Indonesia needs suitable media and communicators to prevent the spread of the covid-19 virus. Therefore, as a social media with several users, Instagram has given birth to massive influencers to spread information digitally. Influencers' existence on social media Instagram can impact anyone, including their followers, by uploading content by inserting educational and socialization messages. This study explores the role of several influencers on Instagram to help the government prevent the spread of the covid-19 virus. The research was conducted qualitatively with a literature review approach and indirect interviews with influencer followers. The results show that influencers' role impacts their followers based on the content they have uploaded and the information they write on their Instagram social media. The educational content on Instagram influencers that are most viewed and responded to contains the importance of washing hands and using hand sanitizers, masks when going out, and education about the importance of social distancing. Influencers content that get the most reactions and viewers are disseminating education about according to the SOP when leaving the house. Several uploads of influencers who go directly to the field to help each other prevent the spread of the Covid-19 virus.